2002
DOI: 10.4049/jimmunol.168.6.2676
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking Surface Ig Delays CD40 Ligand- and IL-4-Induced B Cell Ig Class Switching and Reveals Evidence for Independent Regulation of B Cell Proliferation and Differentiation

Abstract: T cells stimulate B cells to divide and differentiate by providing activating signals in the form of inducible membrane-bound molecules and secreted cytokines. Provision of these signals in vitro reproduces many of the consequences of T-B collaboration in the absence of any form of Ag stimulation. Although clearly not obligatory, Ag signals appear to play an important regulatory role in numerous aspects of the B cell response. To examine directly the effect of an Ag signal, naive B cells were stimulated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…To address this idea, αIgM was added to both the LPS plus IL-4 and αCD40 plus IL-4 activations. Surprisingly, the addition of αIgM suppressed the class switch recombination observed in both activations, which has also been observed by others in cells stimulated through the CD40 receptor (Rush et al, 2002;Thomas et al, 2007). We show here that this was not due to lack of AID, since AID was expressed in all activations.…”
Section: Discussionsupporting
confidence: 58%
“…To address this idea, αIgM was added to both the LPS plus IL-4 and αCD40 plus IL-4 activations. Surprisingly, the addition of αIgM suppressed the class switch recombination observed in both activations, which has also been observed by others in cells stimulated through the CD40 receptor (Rush et al, 2002;Thomas et al, 2007). We show here that this was not due to lack of AID, since AID was expressed in all activations.…”
Section: Discussionsupporting
confidence: 58%
“…A long-standing correlation exists between a prolonged G1 phase that enhances the differentiation potential and a shortened G1 phase that diminishes it (Kato and Sherr, 1993;Carroll et al, 1995;Johnson et al, 1993). However, there is experimental evidence in a variety of cell types, including lymphocytes (Rush et al, 2002;Lea et al, 2003), which show that these processes can be separated and need not proceed simultaneously (Brown et al, 2003). Experiments here are consistent with the idea that Fbxo7 promotes the differentiation of pro-B cells: overexpression of Fbxo7 decreased CD43, which is downregulated as B cell mature, and reduction of Fbxo7 levels increased its expression.…”
Section: Discussionmentioning
confidence: 99%
“…4 This finding adds to the growing evidence for unique signaling pathways regulating AID expression through the BCR and other surface receptors. 38,39 These studies have shown that signaling through the BCR delays AID expression and down-regulates certain AID-induced processes, such as class-switching, while having no effect on total transcript and protein levels. Furthermore, costimulation of both the BCR and TLR-4 was enough to dampen CSR in a phosphatidylinositol 3-kinase-dependent manner.…”
Section: Discussionmentioning
confidence: 99%